Insulinoma presenting as alcoholic stupor. Issue 735 (January 1987) - Dandona, P.; Fonseca, V. A.; Mikhailidis, D. P.; Menon, R. K.
Abstract : We report a case of prolonged loss of consciousness due to hypoglycaemia following ethanol abuse in a non-diabetic. The patient also reported symptoms compatible with hypoglycaemia following heavy manual work. Further investigations revealed a pancreatic insulinoma, which was successfully removed surgically. The patient remains asymptomatic 18 months later, despite occasional episodes of ethanol abuse. This case illustrates how heavy exercise and/or alcohol abuse can aggravate spontaneous hypoglycaemia.